Gender interaction in negotiation of meaning among high proficiency ESL learners / Hee Sio Ching - Hee, Sio Ching (2016)
It is claimed that the augmented use of electronic communication has fully embraced and hampered Generation Y interactions (Wei Liu, 2012, Punitha 2008). Due to prolonged use of high technology tools (Punitha, 2008), leading them to rely on e-communication as a preferred tool of communication and somehow isolate them to a new environment (Black, 2010), an environment away from social and learning activities. It rather seems that face to face interaction tend to occur less frequent than e- communication. This study analyses the linguistic output produced by high proficiency ESL learners during face-to-face interaction, focusing on the Generation Y participants born in the year of 1990 – 1996 who have just completed secondary or higher secondary schools. Generation Y consists of those who were born in the year of 1980 – 2000 and are also known as ‘digital natives’ (Prensky, 2001). They are labelled as ‘digital natives’ (Prensky, 2001) because they are the first generation who grew along with the evolvement of high technology, naturally perceptive of digital language (Black, 2010) and highly involved in interacting with advanced technology tools and are used to interacting with their peers within a computer – mediated environment. Currently there are limited studies on negotiation of meaning that have focused on this particular group of learners (Kotter, 2003; Tam, 2009; Bower & Kawaguchi, 2011). Because of this less is known about the patterns of interaction of this particular group of ESL learners in face to face environment. Therefore, this study aims to address this gap (patterns of interaction) by analysing how high proficiency Gen Y learners negotiate meaning. whether gender plays a role in the interaction. iv The participants involved in the study were 15 females and 15 males, 30 in total and paired in a single – gender matched dyads and mixed – gender dyads. Studies have suggested that the familiarity of participants with each other could affect the output of the interactional patterns (Boulima, 1999; Robinson, 2000; Varonis & Gass, 1985b). For this study the familiarity among the participants are considered moderate as they were in their first 6 months of their course and are constantly engaged in group activities. A decision making two – way tasks were utilized to elicit the data and the analysis of the data was based on a framework by Varonis and Gass (1985b) and Pica et. al’s (1989) schema on negotiation routines. The results revealed that the males took greater advantage of the conversation by producing semantic modification as in more ‘talk’ for comprehensible output especially in a mixed – gender dyads as opposed to in the single matched dyads. In terms of number of words and number of turns within the negotiation routines, the males again tended to produce more than the females in both dyads setting. The females, however, have been shown to utilize the conversation for comprehensible input. The evidence points out that the females have greater tendency to acquire the language in signalling during the negotiation of meaning. Hence it can be concluded that the males from Generation Y tend to dominate the language through comprehensible output whereas the females prefer to request for more input in the conversation.